The association between household’s asset ownership and food security: panel data evidence from Bangladesh - Shifat, Zannatul Ferdous; Alam, Mohammad Jahangir; Begum, Ismat Ara; Iqbal, Md Asif; Sarma, Paresh Kumar; McKenzie, Andrew M. (Frontiers in Sustainable Food Systems, 2025)
Food security remains a critical challenge in Bangladesh, with many households experiencing periodic shortages and nutritional deficiencies. It is necessary to ensure a consistent and adequate food supply for its rapidly growing population, amidst economic and environmental vulnerabilities. In light of this, this study looks into the association between food security and household asset ownership, addressing whether increasing asset accumulation can significantly improve food security status among households. Using panel data and the two rounds of comprehensive and inclusive Bangladesh Integrated Household Surveys (BIHS-2015, 2018), a fixed-effects model is used in this study to take endogeneity issues and unobserved heterogeneity into consideration. The food consumption score and per capita calorie consumption are employed to determine food security. The result found that households with productive assets positively and considerably impact the availability of food calories and asset ownership strengthens households’ income-generating capacity. Furthermore, there are additional significant variables that support the ownership of resources, like annual income and farm size, which are closely linked to enhancing calorie intake and food security as well. Enhancing asset ownership among vulnerable households could significantly bolster food security. Moreover, policies aimed at diversifying household assets and improving access to markets can provide a buffer against food insecurity. By focusing on asset-building strategies, policymakers can foster a more resilient food system that ensures consistent access to food for all households while also increasing households’ incomes by owning assets.